2016
DOI: 10.1038/srep27466
|View full text |Cite
|
Sign up to set email alerts
|

The SDF-1 rs1801157 Polymorphism is Associated with Cancer Risk: An Update Pooled Analysis and FPRP Test of 17,876 Participants

Abstract: The stromal cell derived factor-1 (SDF-1) rs1801157 gene polymorphism has been implicated in susceptibility to cancer, but the results were inconclusive. The current study was to precisely investigate the association between SDF-1 rs1801157 polymorphism and cancer risk using meta-analysis and the false positive report probability (FPRP) test. All 17,876 participants were included in the study. The meta-analysis results indicated a significant association between the SDF-1 rs1801157 polymorphism and cancer risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…[ 21 ]. However, we excluded previous metaanalyses performed on variants in GSTM1 , NAT2 [ 2, 25–27 ], GSTP1 [ 25, 28 ], hOGG1 [ 29 ], NQO1 [ 25, 30–32 ], TP53 [ 33 ], XRCC1 [ 34–37 ], XRCC3 [ 25, 38 ], XPC [ 25 ], XPD [ 25 ], PSCA [ 32 ], SDF-1 [ 39 ], TRAIL-R1 [ 40 ], E-cadherin [ 41 ], and TGFBR1 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ]. However, we excluded previous metaanalyses performed on variants in GSTM1 , NAT2 [ 2, 25–27 ], GSTP1 [ 25, 28 ], hOGG1 [ 29 ], NQO1 [ 25, 30–32 ], TP53 [ 33 ], XRCC1 [ 34–37 ], XRCC3 [ 25, 38 ], XPC [ 25 ], XPD [ 25 ], PSCA [ 32 ], SDF-1 [ 39 ], TRAIL-R1 [ 40 ], E-cadherin [ 41 ], and TGFBR1 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in an Asian population the polymorphism was associated with malignancies, but in a Caucasian population this was uncertain. 23 Xia et al found individuals with the A allele of the G801A polymorphism in the CXCL12 gene are under a higher risk for breast carcinoma. 35 Zhang et al demonstrated that SDF1 -3′A polymorphism may be associated with increased risk of hematological malignancy, especially for chronic myeloid leukemia, Hodgkin’s lymphoma, multiple myeloma and the non-Caucasian population.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 An increasing number of studies in recent years have confirmed an association between the CXCL12 rs1801157 polymorphism and the risk of malignancies. 22 , 23 Nevertheless, whether it is associated specifically with the risk of CRC remains controversial. Therefore, this meta-analysis of relevant studies was conducted to investigate further an association between CXCL12 rs1801157 polymorphism and the risk of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…For examples, the significant association between SDF-1 rs1801157 polymorphism and hematological malignancy was observed by Zhang et al based on 9 related studies [ 23 ]. The related pooled analysis carried out by Tong et al suggested that SDF-1 rs1801157 polymorphism showed close association with cancer risk among Asians, especially influencing the susceptibility of urologic and lung cancers [ 24 ]. However, Wang et al found that there were no significant association between SDF-1 rs1801157 polymorphism and coronary hear disease based on 7 articles [ 25 ].…”
Section: Discussionmentioning
confidence: 99%